Pengaturan Penjaminan Polis sebagai Upaya Perlindungan Dana Masyarakat dalam Praktik Perasuransian - Fauzi, Wetria (Nagari Law Review, 2023)
Claiming an insurance policy is a complex issue. Sometimes, insurance companies refuse to pay claims for various reasons and cannot pay policyholders' insurance claims. Therefore, the presence of a policy guarantee institution is essential. Article 53, paragraph (4) of the Insurance Law stipulates that the Law regarding policy guarantee programs shall be formed 3 (three) years after the legalization of the Insurance Law. However, as mandated by Article 53, the policy guarantee institution has yet to be approved. Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector Development and Strengthening of the Financial Sector or PPSK answers this problem. The Law provides a new mandate to form an institution, the Deposit Insurance Corporation (LPS). The existence of a Policy Guarantee Institution as mandated by the Law No. 40 of 2014 concerning Insurance could not be embodied. Therefore, enacting Law No. 4 of 2023 concerning the development and strengthening of the financial sector will hopefully become the answer. This Law provides the duties and authority of the Deposit Insurance Institution (LPS) to guarantee policies to protect public funds. However, to achieve the goal of the new Law, there should be good coordination between the Financial Services Authority (OJK), the financial services industry supervisory institution, and LPS, the policy guarantee institution. These two institutions should synergize with each other in protecting insurance policyholders.